CONCOMITANTPEDIATRICLONGITUDIONAL EXTENSIVE TRANSVERSE MYELITIS (LETM) ANDACUTE MOTOR AXONAL NEUROPATHY (AMAN): CASE REPORT AND LITERATURE REVIEW - Bojadzieva, Sonja Ilija; Duma, Filip; Sofijanova, Aspazija; Murtezani, Avdi; Tankoska, Maja; Ramadani, Atip; Jordanova, Olivera (Journal of Morphological Sciences, 2020)
Acute motor axonal neuropathy (AMAN) is a subtype of Guillain-Barre syndrome (GBS) . AMAN diagnosis is based on decreased compound muscle action potentials (CMAP) and absence of demyelinating findings.We present an 8-year-old boy admitted to our clinic for further evaluation and therapy of an unknown and progressive loss of motor function of the lower extremities. The serum pneumoslide results included: respiratory syncytial virus IgG +/- and Mycoplasma Pneumoniae IgM +/-. Due to positive cerebrospinal fluid (CSF), magnetic resonance imaging (MRI) and electromyography (EMG) findings, diagnosis of longitudinal extensive transverse myelitis (LETM) was established and therapy with intravenous immunoglobulins (IVIg) and pulse corticosteroid therapy was given. After 6 months, a repeat EMG evaluation found an underlying axonal neuropathy with signs of axonal damage, lack of peripheral demyelination, and pathologic F-wave-findings. Due to the clinical worsening and changes in elecrophysiologic findings, additional diagnosis of atypical GBS of acute motor axonal neuropathy was established. After immunomodulatory therapy, gradual recovery of the funcitons occured and the clinical picture stabilzed. Maintenance immunomodulatory therapy was intiated and safely utilized over the following year.Pediatric patients can develop post-infectious or idiopathic occurance of concomitant LETM and AMAN with overlapping neurological symptoms. Succsesful managment of such cases should include both vigilant diagnosis through neurological examination, EMG and MRI,as well as treatment with both acute and maintaining immunomodulatory therapy.  Key words: acute motor axonal neuropathy, Guillain-Barre syndrome, longitudinal extensive transverse myelitis